Analisis Pengaruh Faktor – Faktor Fundamental Makroekonomi Terhadap Kinerja Keuangan Perusahaan Serta Nilai Perusahaan (Studi Kasus Pada Perusahaan Perbankan yang Terdaftar di BEI Periode 2009 – 2013) - Opod, Chrisna Riane (Universitas Sam Ratulangi, 2015)
This research aims to analyze the effects of macroeconomics fundamental factors (Inflation, Interest Rate, Currency Rate, GDP) to the financial firm performance (Cash Ratio, Return on Equity, Debt to Equity) and firm value (Tobin’s Q value). Path analysis is applied to this research. The findings of this research is all of the variables represented macroeconomics fundamental factors ; Inflation (X1), Interest Rate (X2), Currency Rate (X3), GDP (X4) does not have significant effect to the firm performance and form value. Meanwhile, from the variables represented financial firm performance ; CR (Y1), ROE (Y2), DER (Y3) Return on Equity has a significant effect to the firm value (Y4) Keywords: Macroeconomics Fundamental Factors, Financial Firm Performance, Firm Value